Incidence and risk factors of pneumococcal pneumonia in adults: a population-based study - Olga Ochoa-Gondar; Verónica Torras-Vives; Cinta de Diego-Cabanes; Eva M. Satué-Gracia; Angel Vila-Rovira; María J. Forcadell-Perisa; Domingo Ribas-Seguí; Clara Rodríguez-Casado; Angel Vila-Córcoles (BMC Pulmonary Medicine, 2023)
Abstract Background Infection caused by Streptococcus pneumoniae, mainly invasive pneumococcal disease (IPD) and pneumococcal pneumonia (PP), are a major public health problem worldwide. This study investigated population-based incidence and risk of PP among Catalonian persons ≥ 50 years-old with and without specific underlying conditions/comorbidities, examining the influence of single and multi-comorbidities in the risk of suffering PP. Methods Population-based cohort study involving 2,059,645 persons ≥ 50 years-old in Catalonia, Spain, who were retrospectively followed between 01/01/2017-31/12/2018. The Catalonian information system for development of research in primary care (SIDIAP) was used to establish baseline characteristics of the cohort (comorbidities/underlying conditions), and PP cases were collected from discharge codes (ICD-10: J13) of the 68 referral Catalonian hospitals. Results Global incidence rate (IR) was 90.7 PP cases per 100,000 person-years, with a 7.6% (272/3592) case-fatality rate (CFR). Maximum IRs emerged among persons with history of previous IPD or all-cause pneumonia, followed by haematological neoplasia (475.0), HIV-infection (423.7), renal disease (384.9), chronic respiratory disease (314.7), liver disease (232.5), heart disease (221.4), alcoholism (204.8), solid cancer (186.2) and diabetes (159.6). IRs were 42.1, 89.9, 201.1, 350.9, 594.3 and 761.2 in persons with 0, 1, 2, 3, 4 and ≥ 5 comorbidities, respectively. In multivariable analyses, HIV-infection (hazard ratio [HR]: 5.16; 95% CI: 3.57–7.46), prior all-cause pneumonia (HR: 3.96; 95% CI: 3.45–4.55), haematological neoplasia (HR: 2.71; 95% CI: 2.06–3.57), chronic respiratory disease (HR: 2.66; 95% CI: 2.47–2.86) and prior IPD (HR: 2.56; 95% CI: 2.03–3.24) were major predictors for PP. Conclusion Apart of increasing age and immunocompromising conditions (classically recognised as high-risk conditions), history of prior IPD/pneumonia, presence of chronic pulmonary/respiratory disease and/or co-existing multi-comorbidity (i.e., two or more underlying conditions) are major risk factors for PP in adults, with an excess risk near to immunocompromised subjects. Redefining risk categories for PP, including all the above-mentioned conditions into the high-risk category, could be necessary to improve prevention strategies in middle-aged and older adults.